The Cohesion of Poetic Discourse in the Poem Al-Hurūf by the Poet Ahmed Al-Majati - rajwaan, mectafa; tijani, abedrazak (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(--header-height)" dir="auto" data-turn-id="aa22ac62-35fc-428a-a680-05732e0fd3f8" data-testid="conversation-turn-143" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:a6b2ebb2-304a-48ab-8736-5ad337282e90-71" data-testid="conversation-turn-144" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="995a2d7e-c335-48f6-bbc3-49ce28050a6f" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> This study presents itself as a methodological attempt to approach the poetic text in light of the developments in the linguistic field under the term “text linguistics and discourse analysis.” This approach constitutes a scientific study with clearly defined rules and concepts, aiming to place the poetic text under scholarly discourse analysis. It adopts a comprehensive approach, without excluding any participant or element involved in its composition.